1989
DOI: 10.3354/meps054149
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon flux through a Delaware Bay salt marsh: tidal exchange, particle size distribution, and storms

Abstract: Organic carbon exchange via tidal transport between a 190 ha Spartina alterniflora marsh and Delaware Bay was quantified during 5 seasonal sampling periods in April, June, August, October, 1980 and January, 1981. Based on hourly samples collected over 3 consecutive tidal cycles, mean ebb tide concentrations of particulate organic carbon (POC) were hlgher than flood tide concentrations, except in January when the marsh surface and creeks were frozen. Mean ebb tide dissolved organic carbon (DOC) concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…This higher abundance of infauna adjacent to natural marsh habitats as compared to anthropogenically altered shorelines also occurs in the York and Elizabeth-Lafayette Rivers (Seitz et al, 2006). This is most likely driven by differences in allochthonous carbon inputs between the marshes and the hardened shorelines (Quan et al, 2007;Roman and Daiber, 1989;Seitz et al, 2006;Wainright et al, 2000), though differences in water flow (which we did not measure) may also have contributed (Seitz et al, 2006). Additionally, bulkheads are often made of CCA-treated wood, which can have a negative effect on benthic organisms (Weis et al, 1998); however, in this system, riprap, not bulkheads, had the lowest density of benthic macrofauna, and its benthic community differed more from the marshes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This higher abundance of infauna adjacent to natural marsh habitats as compared to anthropogenically altered shorelines also occurs in the York and Elizabeth-Lafayette Rivers (Seitz et al, 2006). This is most likely driven by differences in allochthonous carbon inputs between the marshes and the hardened shorelines (Quan et al, 2007;Roman and Daiber, 1989;Seitz et al, 2006;Wainright et al, 2000), though differences in water flow (which we did not measure) may also have contributed (Seitz et al, 2006). Additionally, bulkheads are often made of CCA-treated wood, which can have a negative effect on benthic organisms (Weis et al, 1998); however, in this system, riprap, not bulkheads, had the lowest density of benthic macrofauna, and its benthic community differed more from the marshes.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of bulkheads, this may be due to toxic chemicals leaching from treated lumber (Weis et al, 1998). However, because marshes can supply substantial amounts of allochthonous carbon to subtidal habitats (Quan et al, 2007;Roman and Daiber, 1989;Wainright et al, 2000), replacing them with riprap or bulkheads, which cannot supply such resources, may lower macrofaunal densities (Seitz et al, 2006). Additionally, hardened shorelines are frequently associated with lower densities and smaller sizes of nektonic species Peterson et al, 2000), though not in all cases (Seitz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As for most studies, the flux estimates do not include transfers that might have occurred as a result of floating wrack, surface films, bedload transport, and movement of nekton. The estimates also exclude the fluxes that might have occurred during storms (Chalmers et al 1985, Roman & Daiber 1989.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are fundamental to understanding the roles that salt marshes play in the functioning of coastal waters, and have been the focus of much research over the last 3 decades (early studies reviewed by Nixon 1980, later studies include Roman & Daiber 1989, Dame et al 1991, Williams et al 1992. Based on early studies that showed the elevated primary production of salt marshes, early workers suggested that marshes might be responsible for large-scale exportation of organic material to adjacent waters (Odum & d e la Cruz 1967).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that these episodic events may result in a pulse of POM suspended in the marsh runoff (Chalmers et al 1985;Wolaver and Spurrier 1988). Roman and Daiber (1989) noticed the presence of plant fragments in the ebbtide water under these circumstances and attributed it to vigorous flushing and erosion of the marsh surface. The prospect that halophyte material is flushed off the Zwin marsh during heavy rains and storms remains to be investigated.…”
Section: Shifts In Seston Characteristics After Inundation Of a Europmentioning
confidence: 99%